2019
DOI: 10.1002/adfm.201809011
|View full text |Cite
|
Sign up to set email alerts
|

Analog Circuit Applications Based on All‐2D Ambipolar ReSe2 Field‐Effect Transistors

Abstract: Complementary circuits based on 2D materials show great promise for nextgeneration electronics. An ambipolar all-2D ReSe 2 field-effect transistor (FET) with a hexagonal boron nitride gate dielectric is fabricated and its electronic characteristics are comprehensively studied by temperature dependence and noise measurements. Ambipolar transfer characteristics are achieved owing to the tunable Fermi level of the graphene contact and negligible and 30 meV Schottky barrier heights for the n-and p-channel regimes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 62 publications
(70 reference statements)
1
22
0
Order By: Relevance
“…The electrical performance of the FETs was measured at room temperature in vacuum (<10 −4 Pa) and the ReSe 2 devices exhibited n‐type conduction with an on/off current ratio up to 10 5 (Figure B). The electron mobility of the ReSe 2 device shown in Figure B was estimated to be ∼5.0 cm 2 V −1 s −1 , which is comparable to the mechanically‐exfoliated flakes and superior to CVD‐grown ReSe 2 (Figure C,D), confirming the very high quality of our CVT‐grown samples. The improvement of the mobility can be attributed to the use of Re and Se powder as source materials and the slow growth process under high temperature and high vacuum in comparison with conventional CVD growth.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The electrical performance of the FETs was measured at room temperature in vacuum (<10 −4 Pa) and the ReSe 2 devices exhibited n‐type conduction with an on/off current ratio up to 10 5 (Figure B). The electron mobility of the ReSe 2 device shown in Figure B was estimated to be ∼5.0 cm 2 V −1 s −1 , which is comparable to the mechanically‐exfoliated flakes and superior to CVD‐grown ReSe 2 (Figure C,D), confirming the very high quality of our CVT‐grown samples. The improvement of the mobility can be attributed to the use of Re and Se powder as source materials and the slow growth process under high temperature and high vacuum in comparison with conventional CVD growth.…”
Section: Resultssupporting
confidence: 62%
“…Two-dimensional (2D) rhenium diselenide (ReSe 2 ) is an emerging anisotropic transition metal dichalcogenides (TMDCs) in distorted 1T 0 structure with triclinic symmetry. [1][2][3][4] This structure endows ReSe 2 with many unusual properties, such as weak interlayer coupling and strong in-plane anisotropic optical, 3 electrical, 1,3 and phonon 2 properties and therefore, exhibits great potential for applications in logic inverters, 5 polarizationsensitive photodetectors, 3 and so on. However, the fundamental investigations and the fabrication of proof-of-concept devices on ReSe 2 are highly-relied on 2D flakes mechanically exfoliated from the bulk crystals synthesized via chemical vapor transport (CVT) [5][6][7] method, which does not allow for the controllable and high-throughput preparation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous authors have already demonstrated the existence of a Schottky barrier at the interface of the metal and the layered material, where charge carriers overcome this barrier at higher temperatures and show thermally-assisted tunnelling at lower temperatures 7 . However, it has now been experimentally proven that the small work function difference between graphene and layered materials allows graphene as a transistor contact to reduce the contribution of contact resistance and then form an Ohmic contact, achieving superior device performance 1014 . Recently, these transistors with layered conducting channels connected in-plane have been surpassed by van der Waals heterostructures, formed by the layer-by-layer integration of various 2D materials in the vertical direction.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these transistors with layered conducting channels connected in-plane have been surpassed by van der Waals heterostructures, formed by the layer-by-layer integration of various 2D materials in the vertical direction. This development has opened a whole new class of materials in condensed matter physics, some of which are being recognized as building blocks for the framework of novel three-dimensional (3D) artificial structures 1418 . Pioneering achievements using these vertically stacked heterostructures have been demonstrated in diverse applications, such as logic devices 19 , atomically thin p-n junctions 20 , van der Waals memristors 21 , tunnelling transistors 22 , and even multifunctional electronics 17,19,23 .…”
Section: Introductionmentioning
confidence: 99%